Electro/Fe2+/Persulfate Oxidation of Landfill Leachate Nanofiltration Concentrate Using MMO/TiO2-Ti Anode: A Kinetic Study - Guvenc, Senem Yazici; Can-Guven, Emine; Cebi, Aleyna; Varank, Gamze; Ozkaya, Bestami (SPRINGER INT PUBL AG, 2021)
In this study, the treatment of nanofiltration (NF) concentrate from a landfill leachate treatment plant through the electrooxidation (EO) process was investigated. Experimental studies were conducted in a batch reactor equipped with multi-metal oxide/TiO2 doped Ti anode and Pt doped Ti cathode. Persulfate was added as the oxidant and the performance of Fe-0, Fe2+, and Fe3+ species as catalysts for persulfate activation was compared. Kinetic studies were carried out for chemical oxygen demand (COD) removal from leachate NF concentrate. Maximum COD removal efficiency was obtained by the EO process in which persulfate was added as the oxidant and Fe2+ was used as the catalyst for persulfate activation. Optimum values of the process variables (pH 5, current 2 A, Fe2+ dose 12 mM and persulfate dose: 60 mM) were determined. The COD removal was 77.1% under optimum conditions. The overall COD removal mechanism is well fitted with the pseudo-first-order and second-order kinetic models with R-2 values of > 0.80 under all applied current values. Specific energy consumption calculated for optimum conditions were 73.4 kWh/m(3) and 14.3 kWh/kg COD. The EO process assisted with Fe2+ activated persulfate can be evaluated as an efficient treatment method for leachate NF concentrate treatment.
Keywords: Leachate NF concentrate; Electrooxidation; Persulfate; Energy consumption; Kinetics; ZERO-VALENT IRON; HEAT-ACTIVATED PERSULFATE; DISSOLVED ORGANIC-MATTER; ELECTROCHEMICAL OXIDATION; AQUEOUS-SOLUTIONS; WATER-TREATMENT; ELECTRO-FENTON; FERROUS ION; DEGRADATION; REMOVAL; Environmental Sciences & Ecology